House prices and monetary policy in the euro area: Evidence from structural VARs - Andrea Nocera; Moreno Roma (European Central Bank (ECB), 2017)
We use a Bayesian stochastic search variable selection structural VAR model to investigate the heterogeneous impact of housing demand shocks on the macro-economy and the role of house prices in the monetary policy transmission, across euro area countries. A novel set of identification restrictions, which combines zero and sign restrictions, is proposed. By exploiting the cross-sectional dimension of our data, we explore the differences in the propagation channels of house prices and monetary policy and the challenges they pose in the process of real and nominal convergence in the Eurozone. Among the main results, we find a comparatively stronger housing wealth effect on consumption in Ireland and Spain. We provide new evidence in support of the financial accelerator hypothesis, showing that house prices play an important role in the availability of loans. A significant and highly heterogeneous effect of monetary policy on house price dynamics is also documented.
Keywords: C22; E21; E31; E44; E52; 330; Bayesian Vector Autoregression; house prices; identified VARs; monetary policy; policy counterfactuals